Application of the Talking Stick Technique Question and Answer Method to the Learning Outcomes of Intensive Grade 1 Female Students at TMI Al Amien Prenduan Sumenep-Madura - Musleh Wahid; Nurlaila (Amandemen: Journal of Learning, Teaching and Educational Studies, 2025)
This research is motivated by the decline in learning outcomes of intensive class 1 students at TMI Al Amien Prenduan, the purpose of this study was to determine the effect of the Talking Stick question and answer learning method on student learning outcomes in the materials of tamrin, nushus, fiqh and aqoid. This research is a quantitative research with a quasi-experimental method of nonequivalent posttest only control group design. The sampling technique used in the study used random sampling taking 38% of the population, so that class 1 Intensive A was obtained as an experimental class consisting of 22 students and class 1 Intensive B as a control class consisting of 21 students with a population of 117 students. The results of this study indicate that there is a significant influence between student learning outcomes with the application of the Talking Stick question and answer method (experimental group) and student learning outcomes that are not applied to the Talking Stick question and answer method (control group). Thus the working hypothesis is accepted and the null hypothesis is rejected, namely that there is a significant difference between the learning outcomes of the experimental group and the control group.